MOTS‐c promotes phosphorodiamidate morpholino oligomer uptake and efficacy in dystrophic mice. Issue 2 (18th December 2020) - Ran, Ning; Lin, Caorui; Leng, Ling; Han, Gang; Geng, Mengyuan; Wu, Yingjie; Bittner, Scott; Moulton, Hong M; Yin, HaiFang
Abstract: Antisense oligonucleotide (AO)‐mediated exon‐skipping therapies show promise in Duchenne muscular dystrophy (DMD), a devastating muscular disease caused by frame‐disrupting mutations in the DMD gene. However, insufficient systemic delivery remains a hurdle to clinical deployment. Here, we demonstrate that MOTS‐c, a mitochondria‐derived bioactive peptide, with an intrinsic muscle‐targeting property, augmented glycolytic flux and energy production capacity of dystrophic muscles in vitro and in vivo, resulting in enhanced phosphorodiamidate morpholino oligomer (PMO) uptake and activity in mdx mice. Long‐term repeated administration of MOTS‐c (500 μg) and PMO at the dose of 12.5 mg/kg/week for 3 weeks followed by 12.5 mg/kg/month for 3 months (PMO‐M) induced therapeutic levels of dystrophin expression in peripheral muscles, with up to 25‐fold increase in diaphragm of mdx mice over PMO alone. PMO‐M improved muscle function and pathologies in mdx mice without detectable toxicity. Our results demonstrate that MOTS‐c enables enhanced PMO uptake and activity in dystrophic muscles by providing energy and may have therapeutic implications for exon‐skipping therapeutics in DMD and other energy‐deficient disorders. Synopsis: This study demonstrates the use of MOTS‐c peptide to promote oligonucleotides uptake in muscle cells by augmenting glycolytic flux and energy production. This approach may be used to improve the success of DMD exon‐skipping therapy and potentially be used for other diseases with hallmarks of energy deficiency. The MOTS‐c resulted in increased ATP levels in dystrophic muscles. Co‐administration of MOTS‐c and low doses of PMO induced 25‐fold increase of dystrophin expression in dystrophic mice. PMO with MOTS‐c improved muscle function and pathologies in dystrophic mice. Abstract : This study demonstrates the use of MOTS‐c peptide to promote oligonucleotides uptake in muscle cells by augmenting glycolytic flux and energy production. This approach may be used to improve the success of DMD exon‐skipping therapy and potentially be used for other diseases with hallmarks of energy deficiency.